Early repolarization as a predictor of arrhythmic and nonarrhythmic cardiac events in middle-aged subjects - Junttila, M. Juhani; Tikkanen, Jani T.; Kenttä, Tuomas; Anttonen, Olli; Aro, Aapo L.; Porthan, Kimmo; Kerola, Tuomas; Rissanen, Harri A.; Knekt, Paul; Huikuri, Heikki V. (Heart rhythm, 2014)
Early repolarization (ER) in the inferior/lateral leads predicts mortality, but whether ER is a specific sign of increased risk for arrhythmic events is not known. The purpose of this study was to study the association of ER and arrhythmic events and nonarrhythmic morbidity and mortality. We assessed the prognostic significance of ER in a community-based general population of 10,846 middle-aged subjects (mean age 44 ± 8 years). The end-points were sustained ventricular tachycardia or resuscitated ventricular fibrillation (VT-VF), arrhythmic death, nonarrhythmic cardiac death, new-onset atrial fibrillation (AF), hospitalization for congestive heart failure, or coronary artery disease during mean follow-up of 30 ± 11 years. ER was defined as ≥0.1-mV elevation of J point in either inferior or lateral leads. After including all risk factors of cardiac mortality and morbidity in Cox regression analysis, inferior ER (prevalence 3.5%) predicted VF-VT events (n = 108 [1.0%]) with a hazard ratio (HR) of 2.2 (95% confidence interval [CI] 1.1–4.5, P = .03) but not nonarrhythmic cardiac death (n = 1235 [12.2%]), AF (n = 1659 [15.2%]), congestive heart failure (n = 1752 [16.1%]), or coronary artery disease (n = 3592 [32.9%]) (P = NS for all). Inferior ER predicted arrhythmic death in cases without other QRS complex abnormalities (multivariate HR 1.68, 95 % CI 1.10–2.58, P = .02) but not in those with ER and other coexisting abnormalities in QRS morphology (HR 1.30, 95% CI 0.86–1.96, P = .22). ER in the inferior leads, especially in cases without other QRS complex abnormalities, predicts the occurrence of VT-VF but not nonarrhythmic cardiac events, suggesting that ER is a specific sign of increased vulnerability to ventricular tachyarrhythmias.